HUMANISTIC RISKS OF DIGITAL DEVELOPMENT OF SOCIETY: ANALYSIS OF WORKS BY FOREIGN AUTHORS - Olga N. Goryacheva; Marina G. Yakovleva (Sovremennye Issledovaniâ Socialʹnyh Problem, 2022)
Digitalization is one of the most factors in the development of postmodern societies. Building an information society with the introduction of digital technologies in various spheres of life is provided for by national programs of various states, including Russia. Despite advantages of this transformation of the social system, the digital technological vector of the development of societies also contains significant risks. The aim of the work is to identify the humanistic risks of digitalization social system. The methodological basis of the research were the theory of the social system by N. Luhmann, the concept of microphysics of power by M. Foucault, the analysis of the logic Big Data by N. Boltz, research in the field of sociology of things by V. Vakhstein. The authors have identified a principles of functioning social digital environment that contradict the humanistic traditions of democratic societies with their ensuring the rights and freedoms of citizens. Among such principles are the principle of totality, the principle of transparency, the principle of objectification and the principle of programming social practices. The results of the research have practical potential in the development of programms for building a digital society.